Sustainability of building elements in Bidayuh traditional longhouse construction / Janet Victoria ... [et al.] - Victoria, Janet; Siti Akhtar, Mahayuddin; Wan Akmal Zahri, Wan Zaharuddin; Siti Norlizaiha, Harun; Balkhiz, Ismail; Noorsaidi, Mahat (2015)
The traditional longhouse is facing challenges in maintaining the sustainable concept, form and antiquity of the building elements. Nowadays, the traditional longhouse is faced with demolishment where it needs to give way to the construction of the single dwellings. Not only that, the existing traditional longhouse struggles to maintain its original concept and antiquity while it struggles with modernization. Thus, it is important to understand the sustainability of the building elements of the traditional longhouse in terms of space concept, layout, materials and method of construction. Later, the preservation of one of Sarawak‟s unique architecture will become possible. A study has been conducted to identify the sustainability of the building elements in Bidayuh longhouse and its relevance in the present and future construction of the longhouse. From the case study that focus on Bidayuh longhouse located at Serian area in Sarawak, Malaysia, the building elements of the Bidayuh longhouse which still stand the test of time will be obtained.